Role of Investigating Thrombophilic Disorders in Young Stroke - Kay W. P. Ng; Pei K. Loh; Vijay K. Sharma (Stroke Research and Treatment)
Our knowledge about various inherited and acquired causes of thrombophilic disorders has increased significantly during the past decade. Technology for various diagnostic tests for these rare disorders has matched the rapid advances in our understanding about the thrombophilic disorders. Inherited thrombophilic disorders predispose young patients for various venous or arterial thrombotic and thromboembolic episodes. Our understanding has also improved about various gene-gene and gene-environment interactions and their impact on the resultant heterogenous clinical manifestations. We describe various thrombophilic disorders, their diagnostic tests, pathogenic potential in isolation or with other concurrent inherited/acquired defects and possible therapeutic and prophylactic strategies. Better understanding, optimal diagnostic and screening protocols are expected to improve the diagnostic yield and help to reduce morbidity, disability, and mortality in relatively younger patients harbouring these inherited and acquired thrombophilic disorders.